In vitro inhibitory activities of magnolol against Candida spp. - Zhou, Peiru (Drug Des Devel Ther, 2017)
Candida spp. cause various infections involving the skin, mucosa, deep tissues, and even life-threatening candidemia. They are regarded as an important pathogen of nosocomial bloodstream infection, with a high mortality rate. As a result of prolonged exposure to azoles, the therapeutic failure associated with azoles resistance has become a serious challenge in clinical situations. Therefore, novel, alternative antifungals are required urgently. In the present study, the CLSI M-27A broth microdilution method and the 2,3-Bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide (XTT) reduction assay were used to evaluate the antifungal effects of magnolol against various standard Candida strains in planktonic mode and biofilm formation, respectively. The antifungal activity of magnolol was demonstrated in planktonic C. albicans and non-albicans Candida species, especially fluconazole-resistant Candida krusei, with the minimum inhibitory concentrations ranging from 10 to 40 μg/mL. The BMIC(90) (minimum concentration with 90% Candida biofilm inhibited) values of magnolol ranged from 20 to 160 μg/mL, whereas the BMIC(90) values of fluconazole were more than 128 μg/mL. As an alternative and broad-spectrum antifungal agent, magnolol might be of benefit to the treatment of refractory Candida infection.